Online Support Group For Chronic Disease Patients in The Context of Health Communication on Social Media - Azizun Kurnia Illahi (Jurnal Komunikasi, 2024)
In the context of health communication, support groups are believed to act as a protective measure against detrimental physical and psychological effects for patients by promoting adaptation both endocrinologically (related to hormones), cognitively, and behaviorally. Such adaptation also brings benefits in enhancing the immune system, adherence to medication consumption, and improving patient health. Support groups are crucial for patients, especially those with similar conditions, as there is a higher level of empathy, mutual information sharing, messages of hope and inspiration, and a platform for expression to enhance the life expectancy of patients with chronic diseases. These support groups emerged since the 1970s, constituting an integral component of healthcare. The existence of support groups is closely linked to helping improve health outcomes and reduce patient mortality rates. The diagnosis given by doctors to individuals can be a traumatic event. In such conditions, effective support systems are needed. These support systems can include friends, family, doctors, or other patients who have experienced similar illnesses. The similarity among members of the support group makes them a "support system" capable of providing both physical and psychological benefits and increasing adherence to the treatment process. The difficulties experienced by patients and their families in managing chronic diseases become highly complex when they do not receive support from their social environment. This motivates the existence of online support groups, which provide them with the flexibility to exchange information and discuss their health problems. To achieve the goals of this research, the researcher used content analysis with the object being the posts of HGM Community  from September to December 2022, while the unit of analysis used was proportional analysis unit. This research found that the most frequently used form of support by group members was instrumental support. The results from 149 posts in HGM Community posts obtained in this study showed that instrumental support with the category of "problem-solving" was the most commonly found.